Peranan Untung Surapati di Wilayah Mataram dalam Babad Trunajaya-Surapati - Guntur Sekti Wijaya; Achmad Zulfikar N.; Alhadisatur Rofiqoh; Dwi Rofikoh; Widayawati Widayawati; Khusnul Villah; Puji M. Arfi; Syahrul Ramadhan W. (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
Babad Trunajaya-Surapati tells about the life journey of a character named Untung, a child who came from Bali. This study aims to determine the role of Untung Surapati in Mataram based on Babad Trunajaya-Surapati. This study uses qualitative method based on the main literature of which has been rewritten in Indonesian as well as the delicate Javanese language written by Sudibjo Z. H. and translated by Soeparmo (2011). The results of this study are (1) The story of Untung Surapati, (2) The background of the arrival of Untung Surapati to Mataram, and (3) The role of Untung Surapati in Mataram based on Babad Trunajaya-Surapati. Overall, it can be seen that the role of Untung Surapati in the Mataram was recorded in Babad Trunajaya-Surapati.